Cognition, optimism and the formation of age-dependent survival beliefs - Nils Grevenbrock; Max Groneck; Alexander Ludwig; Alexander Zimper (Leibniz Institute for Financial Research SAFE, 2020)
This paper investigates the roles psychological biases play in deviations between subjective survival beliefs (SSBs) and objective survival probabilities (OSPs). We model deviations between SSBs and OSPs through age-dependent inverse S-shaped probability weighting functions. Our estimates suggest that implied measures for cognitive weakness and relative pessimism increase with age. We document that direct measures of cognitive weakness and motivational attitudes share these trends. Our regression analyses confirm that these factors play strong quantitative roles in the formation of subjective survival beliefs: cognitive weakness rather than optimism is an increasingly important contributor to overestimation of survival chances in old age.
Keywords: D83; D91; I10; 330; Subjective Survival Beliefs; Probability Weighting Function; Confirmatory Bias; Cognition; Optimism; Pessimism